1993
DOI: 10.1002/eji.1830230707
|View full text |Cite
|
Sign up to set email alerts
|

Allergen exposure induces the activation of allergen‐specific Th2 cells in the airway mucosa of patients with allergic respiratory disorders

Abstract: Biopsy specimens were obtained from the bronchial or the nasal mucosa of three patients with grass pollen-induced bronchial asthma or rhinitis 48 h after positive bronchial or nasal provocation test with grass pollen extract. T cell clones (TCC), derived from these and control specimens, were then assessed for their phenotype, allergen-specificity, profile of cytokine secretion and ability to provide B cell help for IgE synthesis. Out of 50 and 61 CD4+ TCC derived from the bronchial mucosa of the two patient w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
171
1
5

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 337 publications
(182 citation statements)
references
References 28 publications
5
171
1
5
Order By: Relevance
“…There was a significant correlation between the number of CD4 ϩ cells in BAL fluids and the degree of AHR in asthmatic patients (34). Increasing evidence suggests that T lymphocytes, in particular CD4 ϩ T cells of the Th2 type, play an essential role in the development of the eosinophilic inflammatory response commonly found in asthma (35,36). Elevated IL-4, IL-5, and IL-13 levels in bronchial biopsies (36, 37), BAL cells, and blood (37) of allergic asthmatic patients have been reported, and therefore, it is suggested that these Th2-type cytokines play a key role in the eosinophil accumulation and resultant AHR found in asthmatics.…”
Section: Discussionmentioning
confidence: 95%
“…There was a significant correlation between the number of CD4 ϩ cells in BAL fluids and the degree of AHR in asthmatic patients (34). Increasing evidence suggests that T lymphocytes, in particular CD4 ϩ T cells of the Th2 type, play an essential role in the development of the eosinophilic inflammatory response commonly found in asthma (35,36). Elevated IL-4, IL-5, and IL-13 levels in bronchial biopsies (36, 37), BAL cells, and blood (37) of allergic asthmatic patients have been reported, and therefore, it is suggested that these Th2-type cytokines play a key role in the eosinophil accumulation and resultant AHR found in asthmatics.…”
Section: Discussionmentioning
confidence: 95%
“…Atopic disease is characterized by an individual predisposition to develop IgE mediated allergies against environmental allergens (Ishizaka and Ishizaka, 1971) and a Th2-polarized immunity (Del Prete et al, 1993). Atopic patients have an enhanced ability to produce IL-4, not only in response to allergens, but also to other antigens (Parronchi et al, 1992), and in line with this, atopic disease is associated with low IFN-γ secretion (Parronchi et al, 1991;Shimojo et al, 1996)).…”
Section: Introductionmentioning
confidence: 99%
“…IL-5-and IFN-g-positive cells have been identified in biopsies and bronchoalveolar lavage fluid (BALF) from asthmatic subjects [4]. In bronchial biopsies or BALF, after allergen challenge, many allergen-specific T cells are found which are of the Th2 phenotype [5,6], whereas in chronic asthmatic subjects, in whom cells have been recovered without allergen challenge, T cells are predominantly of the Th0 or Th1 phenotype [7].…”
Section: Introductionmentioning
confidence: 99%